miR-191: an emerging player in disease biology - Nagpal, Neha; Kulshreshtha, Ritu (Frontiers in Genetics, 2014)
Specific microRNAs have emerged as key players in disease biology by playing crucial role in disease development and progression. This review draws attention to one such microRNA, miR-191 that has been recently reported to be abnormally expressed in several cancers (>20) and various other diseases like diabetes-type 2, Crohn’s, pulmonary hypertension and Alzheimer’s. It regulates important cellular processes such as cell proliferation, differentiation, apoptosis and migration by targeting important transcription factors, chromatin remodelers and cell cycle associated genes. Several studies have demonstrated it to be an excellent biomarker for cancer diagnosis and prognosis leading to two patents already in its kitty. In this first review we summarize the current knowledge of the regulation, functions and targets of miR-191 and discuss its potential as a promising disease biomarker and therapeutic target.